Association of type 1 diabetes and concentrations of drinking water components in Newfoundland and Labrador, Canada. Issue 1 (21st February 2018) - Chafe, Roger; Aslanov, Rana; Sarkar, Atanu; Gregory, Peter; Comeau, Alex; Newhook, Leigh Anne
Abstract : Objective: To determine the association between drinking water quality and rates of type 1 diabetes in the Newfoundland and Labrador (NL) population, which has one of the highest incidences of type 1 diabetes reported globally. Research design and methods: The study used a community-based, case-control design. We first calculated incidence rates of type 1 diabetes at the provincial, regional and community levels. The connection between incidence rates and components in public water supplies were then analyzed in three ways: to evaluate differences in water quality between communities with and without incident cases of type 1 diabetes, and to analyze the relationship between water quality and incidence rates of type 1 diabetes at both the community and regional levels. Results: The provincial incidence of type 1 diabetes was 51.7/100 000 (0-14 year age group) for the period studied. In the community-based analysis, there were significant associations found between higher concentrations of arsenic (β=0.268, P=0.013) and fluoride (β=0.202, P=0.005) in drinking water and higher incidence of type 1 diabetes. In the regional analysis, barium (β=−0.478, P=0.009) and nickel (β=−0.354, P=0.050) concentrations were negatively associated with incidence of type 1 diabetes. Conclusions: We confirmed the high incidence of type 1 diabetes in NL. We also found that concentrations of some components in drinking water were associated with higher incidence of type 1 diabetes, but no component was found to have a significant association across the three different levels of analysis performed.